Feed Insects as a Reservoir of Granadaene-Producing Lactococci - Neuzil-Bunesova, Vera; Ramirez Garcia, Alejandro; Modrackova, Nikol; Makovska, Marie; Sabolova, Monika; Spröer, Cathrin; Bunk, Boyke; Blom, Jochen; Schwab, Clarissa (Frontiers in Microbiology, 2022)
Insects are a natural nutrient source in the diet of many different animal species and are considered a future source of dietary proteins. However, insects are also carriers of potentially pathogenic microbes, posing a danger to food and feed safety. Lactococcus species are frequently used in the food industry, with some species being pathogenic with an unknown mode of action. We report here the occurrence of the haemolytic orange pigmented phenotype of Lactococcus garvieae/petauri/formosensis in the faecal microbiota of golden lion tamarins (Leontopithecus rosalia) and feed larvae (Zophobas atratus). Pan-genome analysis suggested the existence of four subgroups within the L. garvieae/petauri/formosensis group. The presence of cyl cluster similar to Streptococcus agalactiae suggested a similar granadaene like pigment, an orange pigmented cytotoxic lipid produced by group B streptococci. Pigment production by L. garvieae/petauri/formosensis strains was dependent on the presence of the fermentable sugar substrate, with no pigment being observed at pH<4.7. The addition of buffering compounds, or arginine, which can be metabolized to ammonium, restored pigment formation. In addition, pigment formation might be related to the source of peptone. Feed insects were identified as a regular source of L. garvieae/petauri/formosensis based on reanalysis of available 16S rRNA gene libraries, which suggests them as a source for possible transfer to gut microbiota of humans and animals. Edible insects seem to be a possible pathway for the distribution of granadaene producing lactococci, indicating pathogenic risk and zoonotic potential.